ASCEND: A Study of Cardiovascular Events iN Diabetes: Characteristics of a randomized trial of aspirin and of omega-3 fatty acid supplementation in 15,480 people with diabetes - Bowman, L; Mafham, M; Stevens, W; Haynes, R; Buck, G; Collins, R; Armitage, J; ASCEND Study Collaborative Group (Elsevier, 2017)
Objectives The use of aspirin for the secondary prevention of cardiovascular disease (CVD) is firmly established, and the proportional reductions in heart attacks and strokes appear to be similar in people with and without diabetes. Uncertainty remains about the role of antiplatelet treatments for primary prevention of CVD, and guidelines vary in their recommendations. It has also been hypothesised that long-term aspirin can prevent gastro-intestinal and other cancers. Observational studies suggest associations between higher intakes of omega-3 fatty acids (FA) and lower rates of CVD, but there is no large-scale randomized evidence to support using prophylactic omega-3 FA supplementation in primary prevention. ASCEND is a randomized trial assessing whether 100 mg daily aspirin safely prevents CVD and cancer in patients with diabetes without known arterial disease. It is also assessing whether supplementation with 1 g omega-3 FA daily prevents CVD. This paper describes the methods and baseline characteristics of the randomized participants. Methods and results Between 2005 and 2011, using mail-based methods, 15,480 people with diabetes were randomized to aspirin versus placebo and, in a factorial design, to omega-3 FA supplementation versus placebo. Blood and urine samples were collected to allow baseline stratification by biochemical prognostic variables (e.g. HbA1c, blood lipids). Follow-up is for a median of at least 7 years. Conclusions Demonstrating that prophylactic aspirin safely reduces the risk of CVD or cancer in the primary prevention setting, or that omega-3 FA supplementation prevents CVD, would be relevant to hundreds of millions of people worldwide who are currently not receiving such therapies. The results of ASCEND will be reported in 2018.